(untitled) - Sokolis, Gary E. (Cincinnati, 1997)
Science Probe I & II provide for a two-year high school science requirement with a coordinated approach. The four science disciplines - biology chemistry physics and earth/space science - are connected through a unit-by-unit approach. Offering a solid grounding in science the texts prepare and even motivate students to take additional elective courses as juniors and seniors
Keywords: Science,Science,Thí nghiệm khoa học; Experiments,Juvenile literature,Experiments